2015
DOI: 10.1002/anie.201504126
|View full text |Cite
|
Sign up to set email alerts
|

Fine Tuning of β‐Peptide Foldamers: a Single Atom Replacement Holds Back the Switch from an 8‐Helix to a 12‐Helix

Abstract: Cyclic homologated amino acids are important building blocks for the construction of helical foldamers. N-aminoazetidine-2-carboxylic acid (AAzC), an aza analogue of trans-2-aminocyclobutanecarboxylic acid (tACBC), displays a strong hydrazino turn conformational feature, which is proposed to act as an 8-helix primer. tACBC oligomers bearing a single N-terminal AAzC residue were studied to evaluate the ability of AAzC to induce and support an 8-helix along the oligopeptide length. While tACBC homooligomers assu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 38 publications
3
37
0
Order By: Relevance
“…Thel ower solubility of peptides 5-8 in aprotic solvents (< 1mm in CDCl 3 )precluded similar NMR and IR studies for these compounds.However,the far-UV CD spectra of all a/b/ g-peptides 1-8 were recorded in 0.2 mm MeOH solution and each showed am arked Cotton effect, presenting am inimum around 206 nm and am aximum around 224 nm (Figure 2d). These data compare closely with the methanol-solution signatures of both the 13-helix adopted by b/g-peptides and the 12-helix adopted by b-peptides, [40][41][42] thus suggesting that a/b/g-peptides 1-8 adopt asimilar folded conformation in the same solvent. Collectively,t he NMR, IR, and CD data provide strong evidence that a/b/g-peptides 1-8 are capable of adopting ah ydrogen-bonded helical conformation in hydrogen-bonding and non-hydrogen-bonding solvents.…”
supporting
confidence: 64%
“…Thel ower solubility of peptides 5-8 in aprotic solvents (< 1mm in CDCl 3 )precluded similar NMR and IR studies for these compounds.However,the far-UV CD spectra of all a/b/ g-peptides 1-8 were recorded in 0.2 mm MeOH solution and each showed am arked Cotton effect, presenting am inimum around 206 nm and am aximum around 224 nm (Figure 2d). These data compare closely with the methanol-solution signatures of both the 13-helix adopted by b/g-peptides and the 12-helix adopted by b-peptides, [40][41][42] thus suggesting that a/b/g-peptides 1-8 adopt asimilar folded conformation in the same solvent. Collectively,t he NMR, IR, and CD data provide strong evidence that a/b/g-peptides 1-8 are capable of adopting ah ydrogen-bonded helical conformation in hydrogen-bonding and non-hydrogen-bonding solvents.…”
supporting
confidence: 64%
“…3) AAzC: Comparable in strengtht oC 8i ntrans-ACBC, the bifurcated C8/C5 pattern due to the presence of as econd interaction center (i.e.,t he N(5) atom), as observed in the condensed state, [21] suggests as tructuring feature that shouldp ersist in larger oligopeptides. [62] Finally,t he present study underlines the interest of the gasphase approach to determine the role of local modifications (in particular, heteroatom substitution) of ap eptide backbone on the folding proclivities of its derivatives. This rewarding approachw ill be pursued for the assessment of other heteroatom substitutions in relateds ystems.…”
Section: Discussionmentioning
confidence: 76%
“…Flash column chromatography was performed on silica gel (Merck, 40-63 mm particle size) by standard techniques eluting with solvents as indicated. 1 1-(1-(1-methoxy-3-methyl-1-oxobutan-2-ylamino)-3-methyl-1-oxohexan-2-yloxy)-1-oxo-3-phenylpropan-2-yl)hydrazinecarboxylate (11). Yield: 74% (64 mg); yellow oil; R f ¼ 0.65 (petrol ether/ethyl acetate 2 : 1, v/v).…”
Section: General Methodsmentioning
confidence: 99%
“…Thus, incorporation of only one hydrazino-derivative of trans-2-aminocyclobutanecarboxylic acid caused stabilization of 8-helix over 12-helix conformation for an oligomer length up to 6 residues. 11 Also, heterochiral cyclic oligomers composed of 1 : 1 mixture of a-amino acids and a-hydrazino acids self-assemble into nanotubular structures in solution and solid phase. 12 We have recently designed a small series of hydrazino peptidomimetics and showed that their interaction with DNA and RNA can be nely modulated with the number and relative position of ahydrazino acid(s) within the peptide chain.…”
Section: Introductionmentioning
confidence: 99%